Analisis Teknik Tarikan yang Ideal pada Permainan Tradisional Ketapel: Tinjauan Biomekanika Olahraga - Nonik Rahesti; Fajar Awang Irawan (Journal of Sport Coaching and Physical Education, 2024)
Slingshot is a traditional game that is played not just shooting, but there are several correct techniques to be able to shoot on target. The purpose of this study is to analyze the biomechanics of pulling in the traditional slingshot game. This research uses quantitative methods which are then explained descriptively analytically using the one shot case study method. The samples used in this study were traditional game activists in Semarang Regency. This research data was obtained using kinematic data obtained from the results of video analysis of catapult techniques with the help of Kinovea software version 0.9.5. From the quantitative data obtained, a recap of the slingshot technique consisting of three phases was obtained, namely the preparation phase, the release phase, and the follow through phase. The results of the study found that the analysis of the pull on the traditional slingshot game activists in Semarang Regency was still not good with an average pull in the preparation phase of 98.11 ± 22.956 degrees with a pull angle in the release phase of 103.76 ± 26.22 degrees. The conclusion in this study found that the ideal pulling technique is a pulling movement that forms an angle of approximately 90 degrees on the arm with the body or torque, which is done when the elbow of the pull is parallel to the hand holding the slingshot frame. It is hoped that further research can discuss related to the analysis of the length of pull and shot accuracy